2019
DOI: 10.1039/c9qo00071b
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free oxidative N–N coupling for the synthesis of 1,2,3-triazole compounds withtBuONO

Abstract: A catalyst-free oxidative N–N coupling with tBuONO has been developed for the synthesis of 1,2,3-triazole compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The notable characteristicso ft he present methodology are catalyst and additive-free, mild conditions can be scaled up with excellent efficiency (Scheme 111). [140] On the basis of the literature precedents, ap lausible mechanism for the formation of 1,2,3-benzothiadiazolesw as proposed.F irstly,t he substrate 149 (or 149')r eacts with TBN to give an itroso intermediate (A), which on the nucleophilic attack followed by dehydration yields the desired products (Scheme 112).…”
Section: Oximationmentioning
confidence: 99%
See 1 more Smart Citation
“…The notable characteristicso ft he present methodology are catalyst and additive-free, mild conditions can be scaled up with excellent efficiency (Scheme 111). [140] On the basis of the literature precedents, ap lausible mechanism for the formation of 1,2,3-benzothiadiazolesw as proposed.F irstly,t he substrate 149 (or 149')r eacts with TBN to give an itroso intermediate (A), which on the nucleophilic attack followed by dehydration yields the desired products (Scheme 112).…”
Section: Oximationmentioning
confidence: 99%
“…In 2019, Zhou and Liu group disclosed a catalyst‐free method for the synthesis of diverse 1,2,3‐triazole compounds ( 150 ) via an oxidative N‐N coupling strategy where TBN acts as the nitrogen synthon. The notable characteristics of the present methodology are catalyst and additive‐free, mild conditions can be scaled up with excellent efficiency (Scheme ) …”
Section: Outlines Of the Reactions Involving Tbnmentioning
confidence: 99%
“…In 2021 Severin et al reported the functionalization of nitrous oxide for the synthesis of triazolopyridines and triazoloquinolines, 40 which are useful building blocks for heterocycle synthesis. 42–47 The reaction was performed in two steps, the first consisting of the lithiation of 2-alkylpyridine and 2-alkylquinoline derivatives, and the second one involving nitrous oxide for its functionalization to triazolopyridine and triazoloquinoline scaffolds (see Scheme 1), to be compared with other synthesis strategies like those with t BuONO 48 or azides. 49…”
Section: Introductionmentioning
confidence: 99%
“…3). More recently, Wu et al [16] . have prepared [1,2,3]triazolo[1,5‐ a ]pyridines starting from pyridin‐2‐ylmethanamines, through an oxidative catalyst‐free N−N coupling strategy.…”
Section: Introductionmentioning
confidence: 99%